GOVERNANCE VS ABOLITION OF NUCLEAR WEAPONS: THE PEACE STUDIES APPROACH (Annual of the Faculty of Philosophy in Skopje, 2024)
This article explores how peace studies deal with two interrelated issues: nuclearismand militarism. Nuclearism assumes the practice of spreading nuclear threatsalong with the security thinking and power structures that surround the doomsdayweapons. Militarism is about the deeply embedded belief that military power (includingthe nuclear one) is the only way to preserve one’s national security. In short, today’sworld deals not only with stockpiles of existing weapons but also with the way of thinkingabout their use, reduction or abolition. The general hypothesis is that the academicand intellectual efforts invested in these issues are (self) limited and developed in aclimate of self-censorship and organized hypocrisy. This makes them not only ineffectivebut also prone to the preservation of the global status quo as the best solution for peace inthe world. Scientists are involved in the technical aspects of the weapons management.But scholars from the social sciences and humanities (i.e. where the peace researchersmostly come from) are expected to deal with the deconstruction of the dominant way ofthinking (both in academia and out of it) and promotion of the idea that a different worldis possible. Or the alternative is nuclear holocaust.
Keywords: nuclearism; militarism; peace research; global governance; abolition of nuclear weapons